Seasonal Carbonate Chemistry Dynamics on Southeast Florida Coral Reefs: Localized Acidification Hotspots From Navigational Inlets - Enochs, Ian C.; Manzello, Derek P.; Jones, Paul R.; Stamates, S. Jack; Carsey, Thomas P. (Frontiers in Marine Science, 2019)
Seawater carbonate chemistry varies across temporal and spatial scales. Shallow-water environments can exhibit especially dynamic fluctuations as biological and physical processes operate on a smaller water volume relative to open ocean environments. Water was collected on a bi-monthly basis from seven sites off of southeast Florida (Miami-Dade and Broward counties), including four reefs, and three closely-associated inlets. Significant seasonal fluctuations in carbonate chemistry were observed on reef sites, with elevated pCO2 in the warmer wet season. Inlets demonstrated a more dynamic range, with periodic pulses of acidified water contributing to, on average, more advanced acidification conditions than those found at nearby reefs. Within inlet environments, there was a significant negative correlation between seawater salinity and both total alkalinity (TA) and dissolved inorganic carbon (DIC), which was in contrast to the patterns observed on reefs. Elevated TA and DIC in low salinity waters likely reflect carbonate dissolution as a result of organic matter decomposition. Together, these data highlight the important role that inlets play on shallow-water carbonate chemistry dynamics within southeast Florida waters and underscore the degree to which engineered freshwater systems can contribute to coastal acidification on localized scales.